ANALISIS PENGUJIAN TAHANAN ISOLASI TRANSFORMATOR ARUS 70KV BAY KUNINGAN II DI GARDU INDUK SUNYARAGI CIREBON - Lety Hatiffatul Nur; Ulinnuha Latifa (Politeknik Harapan Bersama Tegal, 2022)
Abstract - At the substation there are equipment that is intended as a transmission regulator, one of which is a current transformer.